The ambassador - Colt, Peter, 1973- (Colt, Peter, 1973- Andy Roark mysteries, 2023)
"Boston, 1985. Gordon Stevenson, the former ambassador of Laos, has been getting death threats, and he demands private investigator Andy Roark take the case. After what Stevenson did during the Vietnam war, though, Roark's almost tempted to cheer the man's would-be assassin on. Then he finds out why he's been headhunted for the job ...."--Publisher.